Exploratory Study on Histamine Content and Histidine Decarboxylase Genes of Gram-positive Bacteria in Hákarl. Issue 7 (9th August 2021) - Belleggia, Luca; Milanović, Vesna; Cesaro, Cristiana; Cardinali, Federica; Garofalo, Cristiana; Aquilanti, Lucia; Osimani, Andrea
ABSTRACT: Hákarl is a fermented fish traditionally produced in Iceland. In the present study, no scientific research has so far discussed the implication of histamine in this food. The first quantification of histamine in ready-to-eat samples of hákarl has been performed. The presence of the hdcA gene of Gram-positive bacteria, directly detected in the food matrix via qPCR, was also assessed. Histamine content was between 8.3 ± 0.8 and 13.2 ± 0.3 mg/Kg, with an overall mean of 10.6 ± 2.0 mg/Kg. Interestingly, the copy number of the hdcA gene carried by Gram-positive bacteria harbored by hákarl was below the detection limit in all the samples. Therefore, although the involvement of such a bacterial group cannot be excluded, the results suggest that the low histamine levels detected in the samples can presumably be associated with the decarboxylase activity of Gram-negative bacteria. The present study represents a step forward in understanding the microbiology of hákarl, although further investigations dealing with the monitoring of both histamine levels and microbiota dynamics during the production process are needed.